-3x+2(4x-9)=-53

Simple and best practice solution for -3x+2(4x-9)=-53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+2(4x-9)=-53 equation:


Simplifying
-3x + 2(4x + -9) = -53

Reorder the terms:
-3x + 2(-9 + 4x) = -53
-3x + (-9 * 2 + 4x * 2) = -53
-3x + (-18 + 8x) = -53

Reorder the terms:
-18 + -3x + 8x = -53

Combine like terms: -3x + 8x = 5x
-18 + 5x = -53

Solving
-18 + 5x = -53

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 5x = -53 + 18

Combine like terms: -18 + 18 = 0
0 + 5x = -53 + 18
5x = -53 + 18

Combine like terms: -53 + 18 = -35
5x = -35

Divide each side by '5'.
x = -7

Simplifying
x = -7

See similar equations:

| 7y-6=13y+6 | | 6x+3x=12y+11 | | 2r^2-8r-42=0 | | 1/31/3x^2-10=18 | | 1/3x-36 | | 14x-61=9 | | X/100(240)=12 | | 8(-2x-4)*12=-52 | | x-3(4)=-9 | | 311=-5(7a-7)-4 | | 9/3.14 | | x-18/24=15/8 | | 18w-17w=18 | | 2(4x+5)=13x+1-5x+9 | | (z-1/6)-(1/3z-1/3)= | | 3x-5(x-2)=-6+4x-32 | | -3.30+y=-7 | | 3x-25=11x-5+2C | | 8(x+5)+8=4x+2 | | 96a+4b=4 | | 5(-9+3y)-2y=7 | | 14=6y+y | | (x-5)(2x+8)= | | 3(6+5y)=-2(-5+4y) | | 216x-162=18(12x-9) | | 31.2p=65.1 | | (3x-24)+2x=2x | | 6(1/2u-2/3) | | 1/2x^2-6=0 | | 7x-3(3x+17)=-37 | | 2x-2+x=x-24 | | Cot/cos=CDC |

Equations solver categories